Parent’s responses to nutrient claims and sports celebrity endorsements on unhealthy foods: an experimental study - Dixon, H.; Scully, M.; Wakefield, M.; Kelly, B.; Chapman, K.; Donovan, Robert (Cambridge University Press, 2011)
Objective: To assess parents’ responses to common, potentially misleading strategies for marketing energy-dense and nutrient-poor (EDNP) child-oriented foods. Design: Between-subjects online experiment to test whether nutrient claims and sports celebrity endorsements on the front of packs of EDNP products lead parents to prefer and rate these foods more favourably. Setting: Australia. Subjects: A total of 1551 parents of children aged 5–12 years, who were the main household grocery buyers. Results: Inclusion of nutrient claims or sports celebrity endorsements on EDNP products led parents to perceive these products to be more nutritious than if they did not include such promotions. When asked to choose between a pair of different products (EDNP v. healthier), 56 % of parents did not read a nutrition information panel (NIP) before making their choice and this did not differ by promotion condition. These parents were more likely to choose an EDNP product if it included a nutrient claim (OR = 1.83, 95 % CI 1.31, 2.56; P < 0.001) or sports celebrity endorsement (OR = 2.37, 95 % CI 1.70, 3.32; P < 0.001). Sports celebrity endorsements also enhanced parent's perceptions of typical consumers of the product, perceptions of product healthiness and quality, as well as purchase intentions. Conclusions: Nutrient claims and sports celebrity endorsements tip consumer preferences towards EDNP products bearing such promotions, especially among the majority who do not read the NIP. As parents largely determine what foods are available to children at home, it is critical that initiatives aimed at reducing the persuasive impact of food marketing include this target group.